Depression after stroke: The role of the GP. Issue 10 (October 2018) - Poppleton, Aaron; Watkins, Caroline; Chauhan, Umesh; Lightbody, Liz
Around a third of people will experience depression after having a stroke. Depression after stroke is associated with reduced quality of life, poorer medication compliance, and greater morbidity and mortality. It has historically been underdiagnosed and undertreated, despite recommendations that all individuals who have had a stroke be screened for mental health problems. The following article describes what is known about depression after stroke, drawing on National Institute for Health and Care Excellence guidelines. Steps to overcome challenges in assessment within general practice are presented, in addition to ways of achieving an effective biopsychosocial management strategy that promotes recovery, community engagement and effective carer support.